2017
DOI: 10.17235/reed.2017.4773/2016
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of peroral endoscopic myotomy compared with other invasive treatment options for the different esophageal motor disorders

Abstract: Short-term outcomes are similar to laparoscopic Heller myotomy (LHM) and pneumatic endoscopic dilation (PD) (clinical success > 90%) for achalasia subtypes I and II. Mid-term outcomes are comparable to LHM and overcome the results obtained after PD (> 90% vs ~50%). With regard to type III achalasia, POEM efficacy is 98% compared to 80.8% for LHM and the PD success remains at 40%. With regard to spastic esophageal disorders (SED), POEM has an effectiveness of 88% and 70% for distal esophageal spasm (DES) and j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 71 publications
2
6
0
3
Order By: Relevance
“…Endoscopic myotomy can be performed on the posterior wall or on the opposite side of the initial incision, with good results regarding symptom regression and no additional adverse events [5,21,[24][25][26][27][28], certifying that previous treatment does not necessarily influence the therapeutic failure. These results were confirmed by other studies as well [7,15,27,29].…”
Section: Discussionsupporting
confidence: 90%
“…Endoscopic myotomy can be performed on the posterior wall or on the opposite side of the initial incision, with good results regarding symptom regression and no additional adverse events [5,21,[24][25][26][27][28], certifying that previous treatment does not necessarily influence the therapeutic failure. These results were confirmed by other studies as well [7,15,27,29].…”
Section: Discussionsupporting
confidence: 90%
“…Since 2008, POEM has proven its efficacy in the treatment of achalasia and it is now considered an alternative first-line therapy by many. POEM can be offered for different esophageal diseases 20 21 22 23 24 25 , is cost-saving 26 , and provides a longer myotomy 21 , with similar long-term benefits as compared to HM 27 28 , while reducing post-procedural pain 29 . In addition, endoscopic myotomy has proven to be a promising technique folr other esophageal conditions, such as Jackhammer esophagus 30 and as a “salvation technique” for patients with recurrent symptoms after HM 31 32 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Proton pump inhibitors can be used in patients with JE [7]. Potential endoscopic approaches are botulinum toxin injection [7, 10], pneumatic dilation [7], and peroral endoscopic myotomy (POEM) [7, 11]. In the study mentioned above, where a patient with JE was found to have an eosinophilic infiltration of the muscularis propria, prednisone was used in combination with POEM [8].…”
Section: Introductionmentioning
confidence: 99%